Low risk of acquiring melioidosis from the environment in the continental United States - Hall, Carina M.; Romero-Alvarez, Daniel; Martz, Madison; Santana-Propper, Ella; Versluis, Lora; Jiménez, Laura; Alkishe, Abdelghafar; Busch, Joseph D.; Maness, Trevor; Stewart, Jonathan; Sidwa, Tom; Gee, Jay E.; et al. (PloS one, 2022)
Melioidosis is an underreported human disease of tropical and sub-tropical regions caused by the saprophyte Burkholderia pseudomallei . Although most global melioidosis cases are reported from tropical regions in Southeast Asia and northern Australia, there are multiple occurrences from sub-tropical regions, including the United States (U.S.). Most melioidosis cases reported from the continental U.S. are the result of acquiring the disease during travel to endemic regions or from contaminated imported materials. Only two human melioidosis cases from the continental U.S. have likely acquired B . pseudomallei directly from local environments and these cases lived only ~7 km from each other in rural Texas. In this study, we assessed the risk of acquiring melioidosis from the environment within the continental U.S. by surveying for B . pseudomallei in the environment in Texas where these two human melioidosis cases likely acquired their infections. We sampled the environment near the homes of the two cases and at additional sampling locations in surrounding counties in Texas that were selected based on ecological niche modeling. B . pseudomallei was not detected at the residences of these two cases or in the surrounding region. These negative data are important to demonstrate that B . pseudomallei is rare in the environment in the U.S. even at locations where locally acquired human cases likely have occurred, documenting the low risk of acquiring B . pseudomallei infection from the environment in the continental U.S.